Customer Retention Program Framework pada Rancang Bangun Sistem Manajemen Hubungan Pelanggan - Achmad Chusni Mubarok; Intan Dzikria (Prosiding Seminar Nasional Teknoka, 2023)
Computer service services are now widely sought after when a computer or laptop device is damaged. But problems arise when customers have to look for and go to a service provider directly at the shop to carry out service or by making a telephone call or WhatsApp. Apart from that, service services rely on promotions through social media or only rely on customer satisfaction through word of mouth. This research aims to design a customer relationship management system for web-based computer repair services that is optimal and efficient based on the customer retention program (CRP) framework. CRP is a part of customer relationship management that focuses on various features that can keep customers coming back. Requirements analysis is carried out by finding functional requirements which are reduced to various design diagrams as the basis for system development. This research carried out black box testing which showed that user needs were met for the CRP framework that was built with the result that 85% of the functionality had passed the requirements test..